2003
DOI: 10.1007/s00221-003-1456-y
|View full text |Cite
|
Sign up to set email alerts
|

Anticipatory postural adjustments while sitting: The effects of different leg supports

Abstract: The aim of this study was twofold, to analyze the effects of changes in body position and changes in the location of body supports on anticipatory postural adjustments (APAs). Eight healthy subjects were studied while sitting and standing. Subjects exerted upward or downward vertical force against an object attached to a rigid frame and released the object with a fast bilateral shoulder abduction movement. While sitting, four support conditions were studied: with and without feet support, and with anterior or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
1
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 32 publications
4
45
1
2
Order By: Relevance
“…In SitTS and StandTS, the forward movement of the trunk over the lower limbs justifies the need of TA activation timing prior to the movement. This is based on the fact that the central nervous system can previously adjust anticipatory activity of muscles in response to perturbations/changes in the direction of the movement (Aruin & Shiratori, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In SitTS and StandTS, the forward movement of the trunk over the lower limbs justifies the need of TA activation timing prior to the movement. This is based on the fact that the central nervous system can previously adjust anticipatory activity of muscles in response to perturbations/changes in the direction of the movement (Aruin & Shiratori, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…An voluntary movement requires an adequate postural control (PC) to the desired action under a particular environment (Bigongiari et al, 2011;MacKinnon et al, 2007), being generally preceded and accompanied by postural adjustments, which have been previously described as anticipatory postural adjustments (APAs) (Aruin, 2002;Aruin & Shiratori, 2003;Ruget et al, 2008). Therefore, the muscles responsible for postural adjustments are activated before those acting as prime movers (Ruget et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The redistribution of weight using the legs is further complicated by their use in applying independent pressure to the hi-hat and bass drum pedals. Consequently, upper body stabilization is carried out by the trunk, specifically the erector spinae (ES) and rectus abdominis (RA), irrespective of the types levels of support in the legs (Aruin & Shiratori, 2003). These findings were supported by Santos and Aruin (2008), who also found that the lateral muscles contributed to upright posture control in feed-forward movements (i.e., movements relying on anticipatory correction), akin to feedforward movements in drumming and where the level of muscle activation being is directionally specific.…”
Section: Bodily Coordinationmentioning
confidence: 99%